Concrete-to-Abstract Transitions and Affective Factors in Fourth-Grade Mathematics: A Systematic Review of Pedagogical Challenges and Merdeka Curriculum Implementation - Setianingsih Setianingsih; Fitrika Asrofatul Arofah; Suyono Suyono; Riska Pristiani (Universitas Negeri Surabaya, 2026)
Fourth grade represents a critical transition period in elementary mathematics education where students encounter increasingly abstract concepts requiring sophisticated pedagogical approaches. This systematic literature review synthesizes 32 empirical studies (2021-2025) examining concrete-representational-abstract (CRA) instructional sequences, affective dimensions, and Merdeka Curriculum implementation challenges in fourth-grade mathematics learning. Analysis reveals three primary findings: First, systematic CRA/CPA progressions significantly enhance conceptual understanding across fractions, geometry, and algebraic thinking, yet classroom implementation frequently exhibits problematic practices including premature abstraction or prolonged concrete manipulation, with the critical pictorial bridging phase often omitted. Second, mathematical self-efficacy, mathematics anxiety, and achievement demonstrate consistent bidirectional relationships, with fourth grade constituting a consequential period for mathematical identity formation. Third, Merdeka Curriculum's numeracy literacy emphasis confronts substantial implementation obstacles including conceptual misconceptions, inadequate professional development, resource limitations, structural constraints, and policy misalignments. Findings indicate that effective fourth-grade mathematics pedagogy requires integrated frameworks simultaneously addressing cognitive-developmental progressions, affective support, contextual meaning-making, and differentiated instruction, supported by systemic reforms encompassing sustained teacher professional development, coherent policy alignment, and adequate resource allocation. This review provides evidence-based recommendations for elementary educators and policymakers designing more effective mathematics learning experiences.